Gender Mainstreaming in Da’wa: Study on the Role of Female Preachers in Samarinda - Hidayati, Diajeng Laily; Wijaya, Ida Suryani; Ridho, Miftahur (Proceedings of International Conference on Da'wa and Communication, 2019)
Da'wa is one form of spreading religion in Islam. At present, the da’wa movement is not only dominated by the 30-50 years age group but also mostly carried out by the younger generation. In practice, da’wa activities are often dominated by male preachers. On the other hand, the phenomenon of da’wa shows that the target of da'wa (mad'u) is dominated by female. Therefore, recently many female preachers began to emerge in the community. This paper aims at looking at gender mainstreaming in da'wa by answering the following questions (1) how is Da’wa movement among young people in Samarinda (2) how is the role of female preachers in spreading Islamic teachings in the community in Samarinda. This paper uses three data collection methods, namely observation, interviews, and documentation. Qualitative descriptive data analysis is used to see the phenomenon of women in a comprehensive manner in the city of Samarinda.